Tourniquet application during anesthesia: "What we need to know?" - Kamal Kumar; Craig Railton; Qutaiba Tawfic (Wolters Kluwer Medknow Publications, 2016)
Tourniquets are routinely and safely used in limb surgeries throughout the world. Tourniquet application alters normal physiology. Healthy patients tolerate these physiological changes well, but the physiological changes may not be well-tolerated by patients with poor cardiac function. This review discusses the physiological changes associated with tourniquet use, safe practice and provides the latest updates regarding tourniquet use. A systematic literature search of PubMed, MEDLINE, ScienceDirect, and Google Scholar was done. The search results were limited to the randomized controlled trials and systemic reviews. The papers are summarized in this review.